PARESIA NEUROMUSCULAR EM VACA HOLANDESA PÓS-PARTO - Junior, Adair Antonio Bulegon; Fraga, Denize Da Rosa; Beck, Cristiane; Pereira, Roberta Carneiro Da Fontoura; Teichmann, Cristiane Elise (Salão do Conhecimento, 2017)
Relato de caso acompanhado durante o Estágio Clínico I em Medicina Veterinária.